Embedded graphs whose links have the largest possible number of components - Huggett, Stephen (Ars mathematica contemporanea, 2015)
We derive the basic properties of graphs embedded on surfaces of positive genus whose corresponding link diagrams have the largest possible number of components.
Keywords: components of links; embedded graphs; komponente povezavnih diagramov; medial; vloženi grafi